2018
DOI: 10.1159/000492890
|View full text |Cite
|
Sign up to set email alerts
|

Memory Impairment Induced by Borna Disease Virus 1 Infection is Associated with Reduced H3K9 Acetylation

Abstract: Background/Aims: Borna disease virus 1 (BoDV-1) infection induces cognitive impairment in rodents. Emerging evidence has demonstrated that Chromatin remodeling through histone acetylation can regulate cognitive function. In the present study, we investigated the epigenetic regulation of chromatin that underlies BoDV-1-induced cognitive changes in the hippocampus. Methods: Immunofluorescence assay was applied to detect BoDV-1 infection in hippocampal neurons and Sprague-Dawley rats models. The histone acetylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…In these non-dividing cells that establish lifelong specialized networks, while remaining able of a high degree of adaptability called plasticity, epigenetic mechanisms are critical regulators. As a result, epigenetic processes of the host cell are also often hijacked by persistent viruses (Bonnaud et al, 2016;Lange et al, 2020;Tarakhovsky and Prinjha, 2018) and BoDV-1 is no exception: our group and others identified BoDV-1 P-mediated ll OPEN ACCESS iScience 25, 103621, January 21, 2022 iScience Article interference with acetylation of Histone H2B and H3 (Bonnaud et al, 2015;Jie et al, 2018). Because DSB can be induced by both P and N proteins, and early DSB accumulation in neurons increases Histone H3 lysine 9 dimethylation (Suberbielle et al, 2015), which corresponds to inhibitory signals of gene expression, it is tempting to speculate that DSB and their signaling may play an upstream role in the further deacetylation of histones.…”
Section: Discussionmentioning
confidence: 94%
“…In these non-dividing cells that establish lifelong specialized networks, while remaining able of a high degree of adaptability called plasticity, epigenetic mechanisms are critical regulators. As a result, epigenetic processes of the host cell are also often hijacked by persistent viruses (Bonnaud et al, 2016;Lange et al, 2020;Tarakhovsky and Prinjha, 2018) and BoDV-1 is no exception: our group and others identified BoDV-1 P-mediated ll OPEN ACCESS iScience 25, 103621, January 21, 2022 iScience Article interference with acetylation of Histone H2B and H3 (Bonnaud et al, 2015;Jie et al, 2018). Because DSB can be induced by both P and N proteins, and early DSB accumulation in neurons increases Histone H3 lysine 9 dimethylation (Suberbielle et al, 2015), which corresponds to inhibitory signals of gene expression, it is tempting to speculate that DSB and their signaling may play an upstream role in the further deacetylation of histones.…”
Section: Discussionmentioning
confidence: 94%
“…15 However, persistently infected rats will have severe hippocampal damage, and slight learning and behavioral impairments can be observed. [13][14][15][16] Our previous studies have shown that BoDV-1 infection can impair the cognitive function of rats, 17,18 but the relevant mechanisms and pathways are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…BoDV-1 strain Hu-H1 was isolated from a patient with bipolar disorder in 1994 [46][47][48]. Cell-free BoDV-1 stock was prepared as described previously [14,49] and used to infect primary cortical neurons.…”
Section: Viral Strains and Cell Linesmentioning
confidence: 99%
“…BoDV-1 replicates in the cell nucleus, a characteristic unique to the order Mononegavirales [4], and persistently infects a wide range of vertebrate species with a broad global geographical distribution [5][6][7][8][9][10]. As a highly neurotropic virus, infection by BoDV-1 leads to a spectrum of neurological diseases ranging from immune-mediated acute fatal encephalitis to non-inflammatory behavioural changes [11][12][13][14][15][16][17][18]. Although the relationship between BoDV-1 and human psychiatric disorders has been controversial for many years [19,20], recently a series of solid evidence suggests that humans could be a target for BDV infection.…”
Section: Introductionmentioning
confidence: 99%